2016
DOI: 10.4269/ajtmh.16-0259
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan Dysfunction Syndrome from Strongyloides stercoralis Hyperinfection in a Patient with Human T-Cell Lymphotropic Virus-1 Coinfection After Initiation of Ivermectin Treatment

Abstract: Abstract. Strongyloides stercoralis is well known to cause hyperinfection syndrome during the period of immunosuppression; but dissemination, worsening hyperinfection, and development of multiorgan dysfunction syndrome after initiation of ivermectin has not been reported in the past. Herein, we describe the case of a 62-year-old man with chronic strongyloidiasis and human T-cell lymphotropic virus-1 coinfection, who developed significant clinical worsening after 24-48 hours of initiation of treatment with iver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In patients co-infected with HTLV-1 and S. stercoralis both parasite antigen-specific IL-5 responses and eosinophil levels were significantly decreased, suggesting an additional means by which the virus infection may impede immunity to helminths. However, rare incidences of acute respiratory distress syndrome have been encountered in HTLV-1-infected patients following treatment with antihelminthics ( 95 ). The mechanisms responsible for the development of this pathology are unknown, but it is plausible that acute immune reactions to the intrapulmonary destruction of the large parasite burden following antihelminthic treatment may play a role in triggering this response ( 95 ).…”
Section: Effects On Viral Infectionsmentioning
confidence: 99%
“…In patients co-infected with HTLV-1 and S. stercoralis both parasite antigen-specific IL-5 responses and eosinophil levels were significantly decreased, suggesting an additional means by which the virus infection may impede immunity to helminths. However, rare incidences of acute respiratory distress syndrome have been encountered in HTLV-1-infected patients following treatment with antihelminthics ( 95 ). The mechanisms responsible for the development of this pathology are unknown, but it is plausible that acute immune reactions to the intrapulmonary destruction of the large parasite burden following antihelminthic treatment may play a role in triggering this response ( 95 ).…”
Section: Effects On Viral Infectionsmentioning
confidence: 99%
“…Our systematic search of the literature for non-neurological adverse events found 10 cases where ivermectin was associated with cutaneous reactions [11][12][13][14][15], nephropathy [16], psychiatric disorders [17,18], hepatic disorders [19,20] and multiorgan dysfunction syndrome [21]. Clinical trials and observational studies have reported common adverse events such as headache, pruritus, muscle pain, cough, dyspnea, nausea, vomiting, diarrhea, blurred vision, postural hypotension and confusion and more anecdotal effects such as serious skin reactions and edematous swelling [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Single-dose ivermectin has recently been evaluated successfully for the treatment of nondisseminated strongyloidiasis in a randomised controlled superiority trial [ 9 ]. Nevertheless, the medical community should be aware that deworming in hyperinfected patients is both essential and at risk of worsening the patient's condition as has been already reported [ 10 ].…”
Section: Discussionmentioning
confidence: 99%